Detection and Characterization of Staphylococcus aureus and Methicillin-Resistant S. aureus in Foods Confiscated in EU Borders - Rodríguez-Lázaro, David; Oniciuc, Elena-Alexandra; García, Patricia G.; Gallego, David; Fernández-Natal, Isabel; Dominguez-Gil, Marta; Eiros-Bouza, José M.; Wagner, Martin; Nicolau, Anca I.; Hernández, Marta (Frontiers in Microbiology, 2017)
The aim of the study was to evaluate the potential role of the illegal entry of food in UE in the MRSA spread. We studied the prevalence and characteristics of Staphylococcus aureus and Methicillin-resistant S. aureus (MRSA) isolated from foods of animal origin confiscated from passengers on flights from forty-five non-EU countries from 2012 to 2015 by the Border Authorities at Bilbao International Airport (Spain) and Vienna International Airport (Austria), as well as foods from open markets close to EU land borders. Of 868 food samples tested (diverse meat samples including antelope, duck, guinea pig, pork, rodents, turkey; dairy products; and eggs), 136 (15.7 %) were positive for S. aureus and 26 (3.0 %) for MRSA. All MRSA strains were mecA-postive. The prevalence of S. aureus-positive dairy samples among food confiscated at Bilbao International Airport was 64.6%, and this airport also had the highest value (11.8%) for MRSA-positive samples. The predominant sequence type was ST5 (30.8%), followed by ST8, ST1649, ST1, and other lineages were found to a lesser extent (ST7, ST22, ST72, ST97 and ST398). Six isolates tested positive for luk-PVL genes (SCCmec IV- subtypes IVc and IVe). Enterotoxin profiling revealed that 19 MRSA strains were enterotoxigenic, harboring one or more se genes. The MRSA isolates positive for luk-PVL genes were not enterotoxigenic, and none of the isolates tested positive for enterotoxin E. We found 14 resistance profiles, and more than 69% of the MRSA isolates were resistant to three or more types of antimicrobial agents. This finding reveals both the wide diversity of the antimicrobial resistance found in the strains and the capacity to resist not only to beta-lactam drugs. One MRSA strain showed unusual characteristics: it was oxacillin-susceptible (OS), harbored SCCmec V, and was positive for sed, seg, and sej but negative for PVL virulence factors. This study shows the presence of enterotoxigenic HA-, CA-, and LA-MRSA in foods illegally entering the EU, and highlights illegal importation of food as route of enterotoxigenic MRSA spread. Uncontrolled entry of food stuffs into the EU can be a relevant neglected route of MRSA dissemination.